2020
DOI: 10.1103/physrevb.101.235206
|View full text |Cite
|
Sign up to set email alerts
|

Towards temperature-induced topological phase transition in SnTe: A first-principles study

Abstract: The temperature renormalization of the bulk band structure of a topological crystalline insulator, SnTe, is calculated using first principles methods. We explicitly include the effect of thermalexpansion-induced modification of electronic states and their band inversion on electron-phonon interaction. We show that the direct gap decreases with temperature, as both thermal expansion and electron-phonon interaction drive SnTe towards the phase transition to a topologically trivial phase as temperature increases.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 71 publications
3
28
1
Order By: Relevance
“…It is observed from the figure that the values of bandgap are monotonically decreasing with increasing the temperature, which have a good agreement with previous theoretical and experimental works on this compound 61,62 . Recent theoretical work on this compound with considering the EPI is also suggesting the similar decreasing nature of bandgap with increasing temperature 18 . From our calculation, the decreasing rate of bandgap with respect to temperature upto 1500 K is found to be in order of 10 −5 , which shows 1/10 times of the previous observation on this compound 45,61 .…”
Section: Finite Temperature Electronic Structurementioning
confidence: 59%
See 2 more Smart Citations
“…It is observed from the figure that the values of bandgap are monotonically decreasing with increasing the temperature, which have a good agreement with previous theoretical and experimental works on this compound 61,62 . Recent theoretical work on this compound with considering the EPI is also suggesting the similar decreasing nature of bandgap with increasing temperature 18 . From our calculation, the decreasing rate of bandgap with respect to temperature upto 1500 K is found to be in order of 10 −5 , which shows 1/10 times of the previous observation on this compound 45,61 .…”
Section: Finite Temperature Electronic Structurementioning
confidence: 59%
“…The extrapolated value of 1st (2nd) peak at 0 K is found to be ∼4 (∼2) meV, which is nicely agreed with the calculated value obtained from ground state G 0 W 0 method. Recently, Querales-Flores et al have shown the temperature dependent ImΣ(ω) which is obtained by considering the EPI 18 . By comparing this with our present work, it suggests that in lower temperature the lifetime of electron due to EPI and EEI are comparable but not in case of higher temperature.…”
Section: Finite Temperature Electronic Structurementioning
confidence: 99%
See 1 more Smart Citation
“…There have been so far several theoretical attempts to tackle this problem. From the single particle density functional theory (DFT) perspective, attempts to assess the topological critical temperature are generally based on the closing of the gap at some finite temperature [7][8][9]. The conjuncture made in these papers is that topological invariants stay unaltered up to this point and the entire physics is determined by the single-particle gap inversion.…”
mentioning
confidence: 99%
“…The explicit changes of the electronic structure due to thermal expansion are taken into account by performing calculations at the temperature-dependent lattice parameter, obtained from the linear thermal expansion coefficient as calculated in Ref. [9]. The electronic dispersion curves near the band edges at L are displayed in Fig.…”
mentioning
confidence: 99%